2021
DOI: 10.30935/ojcmt/11200
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking COVID-19 Vaccine “Infodemic” in the Social Media

Abstract: The activities of the anti-vaccine crusaders and conspiracy theorists on social media platforms have influenced billions of people across the globe on the safety of the COVID-19 vaccines currently been used for immunizations. The increased social media mis/disinformation on the efficacies and safety of these vaccines developed have raised a global concern among all stakeholders. This study adopted a convenience sampling through an online survey to collect data from N=1800 participants (students) from five (5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 22 publications
(32 reference statements)
2
20
1
1
Order By: Relevance
“…In any event, the deployment of effective communication strategies [14] that help to provide targeted information that addresses these questions may be useful. This is particularly important given the negative impact of (dis/mis)information on vaccine behavior around the world [61][62][63]. Scientific communication must take into account readers' and viewers' concerns, should be simple and accessible, and should ideally also be capable of performing well in a social media environment [64].…”
Section: Discussionmentioning
confidence: 99%
“…In any event, the deployment of effective communication strategies [14] that help to provide targeted information that addresses these questions may be useful. This is particularly important given the negative impact of (dis/mis)information on vaccine behavior around the world [61][62][63]. Scientific communication must take into account readers' and viewers' concerns, should be simple and accessible, and should ideally also be capable of performing well in a social media environment [64].…”
Section: Discussionmentioning
confidence: 99%
“…It poses challenges and threats for those who are deceived by fake health information. As suggested by scholars Demuyakor, Nyatuame, and Obiri (2021) governments and stakeholders must carry out massive public education on fact checking. It will reduce the level of panic, fear, and mistrust that false information on social media has brought to the public.…”
Section: Discussionmentioning
confidence: 99%
“…It is followed by nineteenth items that inquire about elements concerning the social support connections of the respondent, with a scale from (1) "Never" to five (5) "Always." It stands out and is characterized for being a short, comprehensible, selfadministered questionnaire which allows to investigate global support in four dimensions: emotional support (questions 3, 4, 8, 9, 13,16,17,19); instrumental support (questions 2, 5, 12, 15); positive social interaction (questions 7, 11, 14, 18); and affective support (questions 6,10,20). In this research, the following reliability indexes were obtained: in emotional support, Cronbach´s Alpha was .96; in instrumental support the index was .88; in positive social interaction it had an index of .93, and in affective support it had an index of .90.…”
Section: Instrumentsmentioning
confidence: 99%
“…In the same manner, a systematic review reveals that scientific production is not enough yet to clarify the impact of SARS-CoV-2 asymptomatic and pre-symptomatic carriers in the disease's propagation [11]. On the other hand, Berberoglu and Dinler [12] demonstrated that communication plays a very important role in the creation of fear towards COVID-19, meanwhile, Demuyakor et al, [13] suggests that people who were exposed to information about COVID-19 vaccine in social media perceived that information as negative and developed higher levels of distrust towards COVID-19 vaccine.…”
Section: Introductionmentioning
confidence: 99%